EMPOWERING EFFECTIVE COMMUNICATION: INNOVATIVE METHODS FOR TEACHING SPEAKING SKILLS - Narzullayeva Sevara; Tohirova Umida Akramovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
With the rapid advancement of technology and the growing need for effective communication, the ability to speak fluently and confidently has become increasingly important across various domains. For educators, the challenge lies in finding innovative methods that engage students and enhance their speaking skills. In this article, we will explore some cutting-edge teaching techniques that can revolutionize the way speaking skills are taught, ensuring students are well-equipped to excel in both academic and professional realms. Speaking plays a crucial role in foreign language teaching and learning. Speaking is the process of building and sharing meaning through the use of verbal and non-verbal symbols, in a variety of contexts.[1] Teaching speaking skills can be a challenging task, but there are several effective methods that educators can use to help students improve their ability to communicate orally. This paper studies several innovative teaching methods, techniques, and activities used for developing speaking fluency and its effects of pupils’ oral competency. [1] Chaney, A.L., and T. L. Burk. 1998. Teaching Oral Communication in Grades K-8. Boston: Allyn & Bacon.